Growth control of differentiated fetal rat hepatocytes in primary monolayer culture. IX. Specific inhibition of DNA synthesis initiation by very low density lipoprotein and possible significance to the problem of liver regeneration (The Rockefeller University Press, 1976)
Rat serum very low density lipoprotein (VLDL) inhibits initiation of DNA synthesis in fetal rat hepatocyte cultures; cells engaged in synthesizing DNA resist inhibition. VLDL action is specific and apparently blocks prereplicative protein synthesis. These and other results, from studies of altered blood VLDL levels and [3H] thymidine incorporation into isolated liver nuclei in 70% hepatectomized normal and mutant hyperlipoproteinemic rats, as well as from infusion studies with a "mitogenic" hormone solution, suggest that hepatic VLDL metabolism is linked to the suppression of hepatocyte proliferation.